A estrutura administrativo-operacional de uma auditoria interna de instituição federal de ensino : um estudo de caso - Brandão, Arthur Pagani (2017)
The present study aimed at verify the current situation of the administrative-operational structure of the Internal Audit of the Federal University of Sergipe, in order to identify areas for improvement in favor of a more efficient and effective performance of the department. In the present study, documentary research was used and the application of the participant observation to the data collection. The results showed that there are aspects to be improved in all categories of analysis used and they have a direct or indirect relationship with the administrative-operational structure of the Internal Audit, linked to the institution that is the subject of its action, in this case the Federal University of Sergipe. In view of the information obtained and with the intention of improving the performance of this department so important for the management and institutional controls of the University, the study proposed the centralization of internal audits of federal educational institutions into a single department directly linked to the Ministry of Education, presenting the positive and negative aspects of such modification, as well as demonstrating the importance of the debate in the scope of the Federal University of Sergipe and of the other federal institutions of education facing such a change.